Příprava a realizace auditu BOZP - Niče, Tomáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
Diplomová práce se zabývá přípravou a realizací auditu BOZP v průmyslovém podniku. V teoretické části jsou popsány současné trendy v oblasti BOZP a dále je věnována pozornost bezpečnosti práce, včetně pracovní úrazovosti v České republice a nových požadavků na systém managementu BOZP dle normy ČSN ISO 45001:2018. V praktické části je představena společnost FORTEX – AGS, a.s., zejména pak středisko Dopravy a mechanizace, kde audit BOZP proběhl. Následně je posouzen zavedený systém managementu BOZP, a to nejprve pomocí analýzy tohoto systému a poté formou interního auditu BOZP, při kterém byly zohledněny též požadavky nové normy ČSN ISO 45001:2018. V poslední části jsou pak navržena doporučení pro zlepšení zavedeného systému managementu BOZP a k získání certifikátu ČSN ISO 45001:2018.

The diploma thesis deals with preparation and implementation of an OHS audit in the industrial enterprise. In the theoretical part, contemporary trends in OHS are described and then attention is kept to the occupational safety, including injury rate in Czech republic and new requirements for occupational health and safety management system according to standard ČSN ISO 45001:2018. In the practical part, company FORTEX – AGS, a.s. is introduced, especially department of transport and mechanization, where was safety audit executed. Then there is assessed occupational health and safety management systém introduced, first by analyzing this system and then by internal audit OHS, in which were requirements new standard ČSN ISO 45001:2018 accounted. At the last part, recommendations are proposed to improvement of occupational health and safety management system and obtaining certificate ČSN ISO 45001:2018.
Preparation and implementation of an OHS audit
Keywords: Bezpečnost a ochrana zdraví při práci (BOZP); systém managementu bezpečnosti; bezpečnostní audit; bezpečnost práce.; Safety nad health at work (OHS); systém of management safety; safety audit; occupational safety.